Images Incorporated / Advertising as Industry and Ideology (Rouledge Sinclair John, 1989)
This book traces the recent history of advertising and provides a critical review of the major theories by which advertising's relationships to economy and culture have been explained. Acknowledgements, The Study of Advertising, Advertising in Econony and Society, Advertising in Cultural Theory, Advertising and Media and Marketing, The Transnationalisation of Advertising, Manufacturing and Marketing and Media in World Regions, Transnational Corporations and Cultural Influence, Advertising and the Future, Bibliography, Index.